Manual on the human rights to safe drinking water and sanitation for practitioners - Bos, Robert; Latorre, Carolina; Alves, David; MacLeod, Neil; Payen, Gérard; Roaf, Virginia; Rouse, Michael J. (IWA Publishing, 2016)
The Manual highlights the human rights principles and criteria in relation to drinking water and sanitation. It explains the international legal obligations in terms of operational policies and practice that will support the progressive realisation of universal access.